Conflict, community, and collaboration: shared implementation barriers and strategies in two polio endemic countries - Eme Owoaje; Ahmad Omid Rahimi; Anna Kalbarczyk; Oluwaseun Akinyemi; Michael A. Peters; Olakunle O. Alonge (BMC, 2020)
Abstract Background Afghanistan and Nigeria are two of the three remaining polio endemic countries. While these two countries have unique sociocultural characteristics, they share major polio risk factors. This paper describes the countries' shared contexts and highlights important lessons on implementing polio eradication activities among hard-to-reach populations relevant for future global health programs. Methods A grey literature review of the Global Polio Eradication Initiative (GPEI) followed by an online survey was conducted in both countries. The survey was targeted to individuals who have been involved continuously in polio eradication activities for 12 months or more since 1988. A sub-set of respondents from the survey was recruited for key-informant interviews (KII). The survey and KIIs were conducted between September 2018-April 2019. A cross-case comparison analysis was conducted to describe shared implementation challenges, strategies, and unintended consequences of polio eradication activities across these contexts. Results Five hundred thirteen and nine hundred twenty-one surveys were completed in Afghanistan and Nigeria respectively; 28 KIIs were conducted in Afghanistan and 29 in Nigeria. Major polio eradication activities in both countries include house-to-house campaigns, cross-border stations, outreach to mobile populations, and surveillance. Common barriers to these activities in both countries include civil unrest and conflict; competing political agendas; and vaccine refusal, fatigue, and mistrust, all of which are all bases for describing hard-to-reach populations. Both countries employed strategies to engage community leadership, political and religious groups through advocacy visits, and recruited community members to participate in program activities to address misconceptions and distrust. Recruitment of female workers has been necessary for accessing women and children in conservative communities. Synergy with other health programs has been valuable; health workers have improved knowledge of the communities they serve which is applicable to other initiatives. Conclusions The power of community engagement at all levels (from leadership to membership) cannot be overstated, particularly in countries facing civil unrest and insecurity. Workforce motivation, community fatigue and mistrust, political priorities, and conflict are intricately interrelated. Community needs should be holistically assessed and addressed;programs must invest in the needs of health workers who engage in these long-term health programs, particularly in unsafe areas, to alleviate demotivation and fatigue.